HIV/AIDS Treatment and Prevention in India : Modeling the Cost and Consequences - Over, Mead; Heywood, Peter; Gold, Julian; Gupta, Indrani; Hira, Subhash; Marseille, Elliot (Washington, DC, 2013)
The three policies analyzed in this document include a minimalist policy in which the government strengthens private sector delivery, an intermediate policy of providing treatment for mothers who have AIDS and their spouses, and a generous policy of providing treatment to the poorest 40 percent of all AIDS patients. In January 2004 the Indian government adopted an AIDS financing policy which contains elements of all three of the hypothetical policies analyzed in this book. This study's projections of the total financial cost of the program and of the cost-effectiveness of the three options can help the government and its partners to plan the scale-up of the existing treatment program, to optimize the mix of components in order to improve its cost-effectiveness and to design monitoring and evaluation measures which provide feedback on program performance.